History of the Youth Pledge in Citizenship Education (PKn) Learning - Harahap, Arsianun (International Journal of Students Education, 2024)
The historical event of Soempah Pemoeda or the Youth Pledge which was declared on October 28, 1928 is a major event in Indonesian history. The Youth Pledge is a commitment of Indonesian youth from various ethnicities and religions to unite to realize an independent Indonesia. The writing of this scientific article uses a data collection method, through literature study . This study was conducted to find the answer to how the sense of one nation among the youth was formed and who the driving force was. The study was conducted using historical methods, using secondary sources. The results of the study show that education has given rise to awareness among the Indonesian people that the ancestors of the Indonesian people were a great nation. Feudalism and colonialism made the Indonesian people a poor, ignorant, and oppressed nation. Educated youth are the driving force behind the struggle of the Indonesian people. The Youth Pledge became a symbol of the spirit of unity and togetherness in the struggle for Indonesian independence. The sense of unity to realize an independent Indonesia is able to eliminate the barriers of difference. Differences in race, nation, language, and religion are eliminated in order to realize unity.